The Botanical City - Jasper, Sandra; Gandy, Matthew (Jovis, 2020)
Roadside "weeds" and other routinely overlooked aspects to urban nature provide a fascinating glimpse into complex global ecologies and new cultures of nature that are emerging across the world. This unique essay collection explores the botanical dimensions to urban space ranging from scientific efforts to understand the distinctive dynamics of urban flora to the way that spontaneous vegetation has inspired artists and writers. The book comprises five thematic sections: histories and taxonomies; botanizing the asphalt; the art of urban flora; experiments in non-design, and cartographic imaginations. The essays explore developments in Berlin, London, Lahore and many other cities, as well as more philosophical reflections on the meaning of urban nature under the putative shift towards the Anthropocen
Keywords: urbaner Raum; städtische Flora; botanische Eigenschaften; Straßenrand; Ökologie; Asphalt; Spontanvegetation; Gewächse; Anthropozän; urbane Natur